(untitled) - Cambridge English language assessment (England, 2017)
Cambridge IELTS 12 provides students with an excellent opportunity to familiarise themselves with IELTS and to practise examination techniques using authentic test material. You can choose an edition containing either four complete tests for Academic or for General Training module. An introduction to these different modules is included in each book, together with an explanation of the scoring system used by Cambridge Assessment English. A comprehensive section of answers and tapescripts makes the material ideal for students working partly or entirely on their own.
Keywords: Anh ngữ,English language; Giáo trình cho người nước ngoài,Textbooks for foreign speakers